2016
DOI: 10.2217/fon-2016-0176
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Damage to Ovary: Mechanisms and Clinical Impact

Abstract: Cancer is a major public health problem around the world. Currently, about 5% of women diagnosed with cancer are of reproductive age. These young survivors may face compromised fertility. The effects of chemotherapeutic agents on ovarian reserve and its clinical consequences are generally inferred from a variety of surrogate markers of ovarian reserve, all aiming to provide prognostic information on fertility or the likelihood of success of infertility treatment. Until recently, the mechanisms that are respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
247
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(251 citation statements)
references
References 74 publications
(97 reference statements)
2
247
0
2
Order By: Relevance
“…Bedschi et al [13] reported that age of the patient and the type and dose of chemotherapy are the main factors determining the magnitude of the damage in the ovary. As for gastric cancer, TS-1 (tegafur, gimeracil, oteracil potassium), which is used as the standard adjuvant chemotherapy for patient with gastric cancer in Japan [14], and CDDP (cisplatin) are classified intermediate and low gonadotoxic chemotherapy respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Bedschi et al [13] reported that age of the patient and the type and dose of chemotherapy are the main factors determining the magnitude of the damage in the ovary. As for gastric cancer, TS-1 (tegafur, gimeracil, oteracil potassium), which is used as the standard adjuvant chemotherapy for patient with gastric cancer in Japan [14], and CDDP (cisplatin) are classified intermediate and low gonadotoxic chemotherapy respectively.…”
Section: Discussionmentioning
confidence: 99%
“…One of the hypotheses for this mechanism comprises the PI3K/PTEN pathway, where the resulting lower local anti‐Müllerian hormone concentrations cause upregulation in the PI3K/PTEN/Akt signaling pathway and lead to less suppression of growth activation . This causes excessive primordial follicle selection, resulting in follicle burn‐out . Furthermore, chemotherapy damages the ovarian stroma and vascularization, and thereby impairs steroidogenesis.…”
Section: Iatrogenic Causes Of Poimentioning
confidence: 99%
“…Ovarian function after chemotherapy depends on the nature of the chemotherapy, the cumulative dosage, and the age when given. Alkylating agents are the most harmful, without a consistent threshold for a safe dose . Prepubertal ovaries seem less vulnerable; early menopause and POI are seen less frequently in prepubertal and adolescent girls after stem cell transplantation …”
Section: Iatrogenic Causes Of Poimentioning
confidence: 99%
See 2 more Smart Citations